Sifat Anti Jamur Kayu Kupa (Syzygium polycephalum (Mig)) (Antifungal Properties of Kupa Wood (Syzygium polycephalum Mig.)) - Renhart Jemi; Wasrin Syafii; Fauzi Febrianto; Muhammad Hanafi (Masyarakat Peneliti Kayu Indonesia, 2010)
The objectives of this research were to evaluate the extractive substances of heartwood of Kupa wood (Syzygium polycephalum (Mig)) and its potention as bio-active substance to wood destroying fungi i.e., Schizophyllum commune Fr and Pleurotus sp. Successive extraction method was used in this experiment. The heartwood part was then converted into 40 mesh wood flour and followed by extraction using methanol, chloroform, ethyl acetate, n-hexane and buthanol solvents. The extractives obtained were subjected to wood destroying fungi S. commune and Pleurotus sp. The results indicated that the extractive content of S. polychephalum mostly dominated by substance diluted in chloroform (2.87%), followed by ethyl acetate (0.38%), n-hexane (0.33%) and buthanol (0.05%). All the wood extracts of S. polychephalum potentially contain anti-fungal compound to inhibit the growth of S. commune Fr and Pleurotus sp fungi. N-hexane and ethyl acetate extracts of S. polychephalum are the most active extracts. Isolation of ethyl acetate fraction resulted in nine (9) active compounds (G.1-G.9) that could inhibit the growth both S. commune and Pleurotus sp with IC(50) values 49.33-61.71 ppm and 48.84-64.61 ppm, respectively. It was found that G.2 compound of ethyl acetate has anti fungal substance namely 3-O-glucosyl-3’,4’ 5-trihydroxyflavonol.